Evaluation methodologies employed in the higher technology course in telematics at Federal Institute of Ceará (IFCE) - Campus Tauá: comparative analysis (Research, Society and Development, 2020)
The research work "Evaluation Methodologies in the Higher Technology Course in Telematics at IFCE - Campus Tauá: Comparative Analysis" surveys, through research among teachers and students of the Telematics course at IFCE - Campus Tauá-Ceará, the methods performance evaluation most used by the faculty versus those that the student body understands as most suitable for measuring their performance in the various disciplines offered by the course. The work also aims to propose a reflection on the evaluation methods used in the field of higher education, more precisely in technological education, in light of the bibliographic contribution of famous authors of education, such as: Freire (2007), Gil (2008), Santo ( 2008), Perrenoud (2000), among others. In conclusion, it is understood that from the constant pedagogical practice, the teacher-student interaction in higher education can always converge to an increasingly collaborative perspective and whose assessment methodology is more and more adherent to the relationships built in the classroom classrooms and laboratories, where the variety of evaluation methods used can reveal more and more fairly the level of involvement and absorption of students in their training process.